Prevalence and predictors of diabetes distress and depression in people with type 1 diabetes - AlOzairi, Abdullah; Irshad, Mohammad; AlKandari, Jumana; AlSaraf, Husain; Al-Ozairi, Ebaa (Frontiers in Psychiatry, 2024)
People living with diabetes often encounter psychosocial challenges, including diabetes distress and depression. Despite this, little research has focused on the co-occurrence of these conditions. This study aimed to explore the prevalence of depressive symptoms and diabetes distress in people with type 1 diabetes in Kuwait and to identify clinical and demographic factors associated with these conditions. A total of 832 people with type 1 diabetes (females: 54.1%, mean age: 29 ± 8.5 years), were invited to participate in Dose Adjustment for Normal Eating (DAFNE) course. Diabetes distress was measured using the Problem Areas in Diabetes (PAID) scale and depressive symptoms were measured using the Patient Health Questionnaire-9 (PHQ-9). Depressive symptoms were defined as PHQ-9 scores ≥10. Data on biomedical outcomes, lifestyle factors, and sociodemographic information were collected. The prevalence rates of diabetes distress and depressive symptoms were 27.8% and 38.3%, respectively. Notably, 19.6% of people experienced both conditions. In the regression analysis, PAID scale and PHQ-9 scores were significantly associated, patients with higher score on depressive symptoms scale were more likely to suffer diabetes distress (B= 2.65, p < 0.001). Female sex (odds ratio [OR]= 2.2, 95% CI= 1.5, 3.2), higher hemoglobin A1c levels (OR= 1.6, 95% CI= 1.0, 2.5), obesity (OR= 1.7, 95% CI= 1.1, 2.8), inactivity (OR= 2.4, 95% CI= 1.6, 3.6), microvascular complications (OR= 2.8, 95% CI= 1.5, 5.4), and lipohypertrophy (OR= 1.7, 95% CI= 1.1, 2.5) were associated with greater odds for the co-occurrence of diabetes distress and depressive symptoms (p< 0.05 for all). The majority of people with type 1 diabetes in Kuwait experience both diabetes distress and depressive symptoms. The strong correlation between diabetes distress and depressive symptoms suggests mutual predictability. The co-occurrence of both symptoms is associated with many sociodemographic and clinical factors.